Effectiveness of Group Counseling Using the Acting As If Technique to Enhance Students’ Assertive Behavior - Sakira Al Anikmah; Ahmad Syarqawi (MASI Mandiri Edukasi, 2025)
This study examines the effectiveness of group counseling, utilizing the Acting As If technique, in promoting assertive behavior among ninth-grade students at Syuhada Sukaraja Private Middle School. Persistent issues with low assertiveness—manifested in difficulties expressing opinions, declining inappropriate peer requests, and communicating confidently—highlighted the need for a structured intervention. A pre-experimental one-group pretest–posttest design was implemented with eight purposively selected students identified as having low assertiveness. Data were collected using a standardised assertiveness questionnaire and analysed using descriptive statistics, the Wilcoxon Signed-Rank Test, and the N-Gain Score. Findings revealed a substantial improvement in assertiveness, with mean scores rising from 46.50 (pretest) to 77.63 (posttest). The Wilcoxon analysis yielded a Z value of −2.524 with a p-value of 0.012 (p < 0.05), indicating a statistically significant change. The N-Gain score of 0.54 (56.46%) placed the intervention in the “moderate” effectiveness category. These results demonstrate that the Acting As If technique—through structured behavioural rehearsal and supportive group interaction—effectively enhances students’ assertive communication skills. The technique offers a practical and replicable counselling approach for enhancing students’ confidence and promoting healthy interpersonal behaviour in school settings.